V.1 - "Guha, Debashis" (New Delhi, 2007)
This volume, The Primer of Applied Ethics, aims at establishing applied and practical Ethics within the broad field of ethics. Concentrating on the Nature and tasks of ethics it traces the Relationship between practical and Professional ethics. Further emphasizing the need for a proper Model of Ethical application, the volume elaborates the nature of a value-laden practical problem awaiting ethical application for a constructive ethical Resolution and formulation of decision-making rules for concerned professionals, in special Context of India. Also, it discusses at length the models of Teaching ethics, including applied ethics. The relevance and Prospects of applied ethics have been highlighted as well.
Keywords: Applied ethics